Comparative Effects of Glenzocimab and Eptifibatide on Bleeding Severity in 2 Mouse Models of Intracranial Hemorrhage - Sébastien Dupont; Héloïse Lebas; Sabrina Mavouna; Eloïse Pascal; Astride Perrot; Adrien Cogo; Marie‐Charlotte Bourrienne; Carine Farkh; Mialitiana Solo Nomenjanahary; Véronique Ollivier; Fatima Zemali; Bernhard Nieswandt; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Antiplatelet drugs represent potential candidates for protecting the penumbral microcirculation during cerebral ischemia and improving the benefits of arterial recanalization in ischemic stroke. Yet while the efficacy of such adjuvant strategies has been shown to be highly time dependent, antiplatelet therapy at the acute phase of ischemic stroke cannot be envisioned until the diagnosis of stroke and its ischemic nature have been confirmed because of the presumed risk of worsening bleeding in case of intracranial hemorrhage (ICH). Here, we investigated this risk for 2 antiplatelet drugs currently being tested in clinical trials for ischemic stroke, glenzocimab and eptifibatide, in 2 mouse models of ICH. Methods and Results The severity of ICH was assessed in mice humanized for glycoprotein VI treated or not with glenzocimab or eptifibatide at effective dose, in a model of primary ICH caused by unilateral striatal injection of collagenase type VII, and in a model of hyperglycemia‐induced hemorrhagic transformation of cerebral ischemia–reperfusion injury. Glenzocimab had no impact on bleeding severity in either model of ICH. Conversely, eptifibatide caused a significant increase in intracranial bleeding in both models, and a drastic increase in death after hyperglycemia‐induced hemorrhagic transformation of cerebral ischemia–reperfusion injury. Conclusions Unlike eptifibatide, glenzocimab is safe in the setting of ICH. These results suggest that glenzocimab could be administered upon suspicion of ischemic stroke, before assessment of its ischemic nature, thus opening the way to hastening of treatment initiation.